Effects of milling methods on the properties of rice flour and steamed rice cakes. (15th September 2022) - Wang, Guozhen; Yan, Xiaoqin; Wang, Bowen; Hu, Xinping; Chen, Xi; Ding, Wenping
Abstract: To investigate the effects of milling methods on the properties of rice flour and steamed rice cakes (SRCs), dry, semi-dry, and wet milling methods were compared. Damaged starch, particle size distribution, water hydration properties, gelatinization properties, gel strength, thermal properties, glass transition temperature, dynamic rheological properties of rice flour, sensory and textural properties of SRCs were evaluated. Semidry-milling rice flour (SF) had much less damaged starch and smaller particle size compared with dry-milling rice flour (DF). The pasting, hydration, and rheological properties of SF were similar to that of wet-milling rice flour (WF). Except for adhesion and appearance, the sensory and textural properties of SF SRCs were significantly better than that of DF SRCs, while comparable to WF SRCs. The results showed that semi-dry milling as an environmental, efficient, and convenient method could provide rice flour suitable to prepare SRCs. In view of sustainable and economic development, semi-dry milling could be a good alternative method in industrial production. Highlights: The steamed rice cakes must be freshly prepared using rice by the wet milling method. Semi-dry milling can emit a little amount of waste water. The rice flour provided by semi-dry milling could be more easily dried and stably stored. Semi-dry milling is an environmental, efficient, and convenient method which is suitable to prepare steamed rice cakes.